2021
DOI: 10.3390/ma14133458
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mechanical Properties of Cr3C2-Ni20Cr/Graphite Cold Sprayed Coatings

Abstract: This study analyzed the mechanical properties of cold-sprayed Cr3C2-25(Ni20Cr) blended with Ni-graphite as a solid lubricant deposited on 7075 aluminum alloy substrate. To optimize the coating properties, different sets of parameters (graphite content in feedstock, process gas composition, spraying distance, and traverse gun speed) were tested in the frame of the Taguchi experiment. The cold-sprayed coatings were evaluated for their chromium carbide and graphite content, hardness, and coefficient of friction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The results corresponded to the higher content of the ceramic phase and lower amount of the graphite built in these deposits and, thus, a greater strain hardening Ni20Cr matrix. This microhardness corresponds with that obtained by Żórawski et al [ 19 ], who investigated the same type of deposits, albeit cold sprayed from the feedstock powder containing a different graphite content, as well as using various spray parameters and working gas combinations. It was also in the range of microhardness (227 HV0.3 to 875 HV0.3) of cold sprayed Cr 3 C 2 -25(Ni20Cr) coatings produced with different parameters of the cold spraying process, but with the use of a powder of the same manufacturer [ 14 , 16 , 17 , 22 ].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The results corresponded to the higher content of the ceramic phase and lower amount of the graphite built in these deposits and, thus, a greater strain hardening Ni20Cr matrix. This microhardness corresponds with that obtained by Żórawski et al [ 19 ], who investigated the same type of deposits, albeit cold sprayed from the feedstock powder containing a different graphite content, as well as using various spray parameters and working gas combinations. It was also in the range of microhardness (227 HV0.3 to 875 HV0.3) of cold sprayed Cr 3 C 2 -25(Ni20Cr) coatings produced with different parameters of the cold spraying process, but with the use of a powder of the same manufacturer [ 14 , 16 , 17 , 22 ].…”
Section: Resultssupporting
confidence: 86%
“…The absence of discontinuities in deposits confirmed the good adhesion of the coatings to the substrates. The above-indicated microstructure features of (Cr 3 C 2 -25(Ni20Cr))-5(Ni25C) composite coatings were observed in the papers of Góral et al [ 16 ] and Żórawski et al [ 19 ], who described in detail the cermet deposit formation during the cold spray process. Image analysis performed using ImageJ software showed that the coatings deposited on the Al alloy substrate had 31.5 ± 1.9 vol.% Cr 3 C 2 and 1.6 ± 0.4 vol.% C, while the coatings deposited on the steel substrate had 32.3 ± 1.3 vol.% Cr 3 C 2 and 1.3 ± 0.2 vol.% C in their structure.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations